Factors associated with the effect of interferon‐α sequential therapy in order to discontinue nucleoside/nucleotide analog treatment in patients with chronic hepatitis B. Issue 12 (4th February 2015) - Matsumoto, Akihiro; Yatsuhashi, Hiroshi; Nagaoka, Shinya; Suzuki, Yoshiyuki; Hosaka, Tetsuya; Tsuge, Masataka; Chayama, Kazuaki; Kanda, Tatsuo; Yokosuka, Osamu; Nishiguchi, Shuhei; Saito, Masaki; Miyase, Shiho; et al.
Abstract : Aim: The factors associated with the outcome of sequential therapy with interferon‐α (IFN‐α) in order to halt nucleoside/nucleotide analog (NUC) maintenance treatment for chronic hepatitis B were analyzed. Methods: A total of 50 patients with chronic hepatitis B who underwent IFN‐α sequential therapy for cessation of NUC were enrolled retrospectively. The subjects received NUC plus IFN‐α for 4 weeks followed by IFN‐α alone for 20 weeks. Natural IFN‐α of 6‐MU doses was administrated three times a week. A successful response to NUC/IFN‐α sequential therapy was defined as serum hepatitis B virus (HBV) DNA below 4.0 log copies/mL, serum alanine aminotransferase (ALT) below 30 IU/L, and hepatitis B e‐antigen negativity at 24 months after completing the treatment. Results: Multivariate analysis revealed that hepatitis B surface antigen (HBsAg) of 3.0 log U/mL or more ( P  < 0.002) and hepatitis B core‐related antigen (hepatitis B core‐related antigen [HBcrAg]) of 4.5 log U/mL or more ( P  < 0.003) at the start of IFN‐α administration were significant factors associated with a 24‐month non‐response. Maximal levels of ALT and HBV DNA during the follow‐up period after completing IFN‐α therapy were significantly related ( P  < 0.001), and receiver operating characteristic analysis showed that both maximal ALT ( P  < 0.001) and HBV DNA ( P  < 0.001) were significantly related to the final 24‐month response. Conclusion: The combinational use of HBsAg and HBcrAg levels may be useful to predict the 24‐month outcome of NUC/IFN‐α sequential therapy. Maximal levels of ALT and HBV DNA during post‐treatment follow‐up may also help monitor responses to IFN‐α sequential therapy.